RETRACTED: Analysis of sustainable investment trends in Russia and worldwide - Batashova Anna; Popova Ellada; Barsukova Svetlana; Chernetskaya Svetlana; Tishchenko Yulia (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001